Conversas ao Pé da Varanda: memórias e narrativas de uma família de sitiantes são-carlenses - Galhardo, Belissa do Pinho Jambersi (2019)
This thesis presents the results of an ethnographic research developed in a farm located in the city of São Carlos. Sought through the field interventions understand and interpret the meanings attributed by the researched interlocutors; to the family, to the land, to the time, to narratives, to the socio-spatial organization and the routine.These aspects were interpreted in the meaning of establishing a relationship between memory and culture in order to understand how the memory attributes meaning and purpose to the culture organized by this family. Thus, from the perspective of this study memory and culture is defined as a meaning attributed to the socially developed practices of the research interlocutors.